Ecology as a Tool to Assist Conservation of a Rare and Endemic Mediterranean Plantago Species - Serrano, Helena Cristina; Pinto, Manuel João; Branquinho, Cristina; Martins-Loução, Maria Amélia (Frontiers in Ecology and Evolution, 2021)
Reviewing the ecological studies on the endangered endemic Plantago almogravensis Franco, an Al-hyperaccumulator plant, and combining these with morphological, physiological, biochemical, and molecular data, significant knowledge on the limiting factors that cause its narrow geographical distribution and rarity status is achieved, which can contribute to suited conservation guidelines. Emphasis was given on (i) the major factors limiting P. almogravensis’ ecological niche (biotic and abiotic); (ii) phases of the life cycle and population dynamics; and (iii) and the phylogenetically close taxa (Plantago subulata aggregate) in order to fill the knowledge gaps in the uniqueness of P. almogravensis ecology, its phylogeny, and conservation status. The identification of relevant ecological data and using plant functional (morphological and physiological) traits, as well as genetic attributes, substantiate into a powerful tool to guide protection and conservation measures, usable toward this and other endangered hyperaccumulator plant species. Knowledge of the limitations of this strongly narrowly distributed plant allows for better design of conservation measures and to guide value and investment strategies in order to secure the species’ current area (habitat conservation and reclamation), direct the expansion of the existing population (assisting in populational densification and colonization), and/or grant ex situ conservation (genetic resources conservation).